Adaptive management and community reaction: The activities of Coastal Action Groups (CAGs) within the shoreline management process in England. (November 2018) - Famuditi, Taye; Bray, Malcolm; Potts, Jonathan; Baily, Brian; Inkpen, Robert
Abstract: Changes in UK government coastal and flooding policies in the last twenty-five years, have resulted in a reappraisal of all coastal defence schemes with a focus on a strategic analysis to ensure that all schemes provided the greatest net benefit. This strategy and the emphasis on adaptive management, particularly in the second wave of shoreline management plans (SMPs), provoked a reaction from local communities who felt their voice was largely being ignored as they became aware of SMP policies that increased their perceived risks but did not offer appropriate compensation. The formation of Coastal Action Groups (CAGs), has been a key community response and enabled diverse communities to feel that they can collectively participate in the ongoing planning process. Using a combination of questionnaire surveys and semi-structured interviews, this paper analyses the nature and effectiveness of CAGs. Although initially formed as opposition groups, the shared ideology of CAG members has resulted in the character of these groups evolving to units that embrace a broader range of social justice issues. It is argued that well led, well-supported, well-resourced and tactically astute CAGs have tended to be the most effective pressure groups. In reality however, CAGs have had relatively limited effects in changing the decisions of local SMPs, but have had great impacts in challenging the concept of meaningful public engagement in the coastal planning process, ultimately leading to more participatory approaches.